2011
DOI: 10.1111/j.1528-1167.2011.03359.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome in PET‐positive, MRI‐negative patients with temporal lobe epilepsy

Abstract: SUMMARYPurpose: Fluorodeoxyglucose positron emission computed tomography (FDG-PET) hypometabolism is important for surgical planning in patients with temporal lobe epilepsy (TLE), but its significance remains unclear in patients who do not have evidence of mesial temporal sclerosis (MTS) on magnetic resonance imaging (MRI). We examined surgical outcomes in a group of PETpositive, MRI-negative patients and compared them with those of patients with MTS. Methods: We queried the Thomas Jefferson University Surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(89 citation statements)
references
References 23 publications
4
81
2
2
Order By: Relevance
“…However, even if the resolution of MRI keeps elevating, there are still many TLE cases in which no meaningful abnormality can be observed. Such cases are classified as MRI- TLE, accounting for approximately 20-30% of TLE [3,4,10,11]. Recently, many MRI- TLE are surgically treated and the prognoses are satisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, even if the resolution of MRI keeps elevating, there are still many TLE cases in which no meaningful abnormality can be observed. Such cases are classified as MRI- TLE, accounting for approximately 20-30% of TLE [3,4,10,11]. Recently, many MRI- TLE are surgically treated and the prognoses are satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…After successful standard anterior temporal lobectomies (sATLs), most patients can achieve excellent outcome. However, epilepsy surgeons frequently run into TLE without meaningful abnormality on MRI, which is the so-called MRI-negative TLE (MRI- TLE), and this accounts for 20-30% of all TLE [3,4]. Multiple one-center retrospective studies reported that the rate of favorable surgical prognosis (Engel grade I + II) of MRI- TLE is approximately 45-90% [2,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLE is traditionally associated with mesial temporal sclerosis (MTS), cell loss, and gliosis in the hippocampus, entorhinal cortex, and amygdala [2]. Currently, surgical intervention is the main choice of treatment for medically intractable TLE [3]. However, surgery helps only 70% of patients become seizure free [4].…”
Section: Introductionmentioning
confidence: 99%
“…(10). MR negatif grupta yapılan çalışmalar bu hastalarda PET'in önemini açık olarak ortaya koymaktadır (11). Hatta farklı bir radyofarmasötik madde olan F-18 FCWAY isimli ajan ile yapılan PET çalışmaları bu ajanın MR negatif grupta FDG'den daha faydalı olabileceğini göstermektedir (12).…”
Section: Epilepsiodağınagörealttiplerunclassified